The Role of Psychological Capital, Subjective Well-Being, and Work Engagement in Improving the Performance of Manufacturing Industry Employees - Yessy Triana Dewi; Evi Susanti; Rina Anindita (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Good human resource management can be leveraged to ensure a company's success. This study aims to determine the relationship between psychological capital, subjective well-being, work engagement, and employee performance. Data was collected by distributing questionnaires to 407 employees of steel billet and iron rod manufacturing companies in Jakarta. The collected data was then analyzed using Structural Equation Modeling (SEM). This study found that high psychological capital is able to improve work engagement and employee performance, but not subjective well-being; high work engagement is able to improve employee performance and subjective well-being, and high employee performance is able to improve subjective well-being. Furthermore, this study found that psychological capital affects subjective well-being mediated by work engagement, while psychological capital does not affect employee performance mediated by work engagement.